Habituasi Nilai Andhap Asor dalam Perilaku Santri di Pesantren - Wahyudi, Heri Fadli; Wardi, Moh.; Jannah, Syaifatul; Hidayati, Nazlah (Proceedings of Annual Conference for Muslim Scholars, 2025)
Individual behavior is not formed suddenly, but is influenced by various factors. In the context of Islamic boarding school education, fostering student behavior is an important aspect, and one of the distinctive values of Islamic boarding schools that can be utilized in fostering behavior is andhap asor. This study aims to find out how Andhap Asor is instilled as a strategy for shaping student behavior. It also examines how the reinforcement and development of Andhap Asor behavior are maintained. This study was conducted using a qualitative field approach, collecting data from informants, namely Kiai, administrators, and students at the Raudlatul Ulum Palongan Islamic Boarding School, Bluto District, through interviews and documentation, which were then analyzed using Huberman's data analysis method. The findings of the study are as follows. First, behavioral training is carried out through the initial stage of theory transfer as a form of stimulus, then reinforced through the reinforcement process and continued continuously with the creation of an environment that reflects the values of Andhap Asor. Second, the Andhap Asor culture developed in Islamic boarding schools is framed in Islamic values, which are instilled through a structured habituation process. Based on these findings, it can be concluded that the behavioral guidance of students at Islamic boarding schools through behavioral counseling strategies can be effective by integrating Andhap Asor values as a cultural foundation. Thus, this strategy not only shapes behavior technically, but also instills character in accordance with the noble values of Islamic boarding schools.